2013
DOI: 10.1016/j.ihj.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Incessant ventricular tachycardia due to multiple cardiac rhabdomyomas in an infant with Tuberous Sclerosis

Abstract: We report a case of incessant ventricular tachycardia managed successfully with medications. The transthoracic echocardiogram showed multiple cardiac rhabdomyomas involving ventricular free wall and outflow tracts. Computerized tomography of brain showed multiple subependymal tubers confirming Tuberous Sclerosis. The follow up assessment showed sinus rhythm and regressing cardiac rhabdomyomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Tachycardia mechanisms have been related to atrial, accessory AV connection reentrant, and ventricular tachycardia. [38][39][40][41][42] Ventricular preexcitation associated with abnormal AV connections has also been commonly reported and has been noted to participate in rapid potentially lifethreatening anomalous AV conduction during atrial fibrillation. [43][44][45] The mechanisms of arrhythmia have often been directly linked to the location of specific cardiac rhabdomyomas.…”
Section: Cardiac Arrhythmia Is a Significant Problem In Tscmentioning
confidence: 99%
“…Tachycardia mechanisms have been related to atrial, accessory AV connection reentrant, and ventricular tachycardia. [38][39][40][41][42] Ventricular preexcitation associated with abnormal AV connections has also been commonly reported and has been noted to participate in rapid potentially lifethreatening anomalous AV conduction during atrial fibrillation. [43][44][45] The mechanisms of arrhythmia have often been directly linked to the location of specific cardiac rhabdomyomas.…”
Section: Cardiac Arrhythmia Is a Significant Problem In Tscmentioning
confidence: 99%
“…Previous study reported that atrial and/or ventricular ectopic beats were seen in 24% of neonates and infants. And other critical arrhythmias, such as pre-excitation syndrome, refractory ectopic AT and incessant VT were demonstrated in cardiac rhabdomyomas [1,7,8]. In the case, nonsustained VT was intermittently observed.…”
Section: Discussionmentioning
confidence: 93%
“…Частыми находками являются различные нарушения ритма сердца, определяемые локализацией рабдомиом. При холтеровском мониторировании ЭКГ часто регистрируются различные нарушения ритма и проводимости сердца: синдром Вольфа -Паркинсона -Уайта, наджелудочковая тахикардия, синдром слабости синусного узла, желудочковая тахикардия [9,10]. По данным литературы, при рабдомиомах сердца часто описываются аномалии ЭКГ.…”
Section: сибирский журнал клинической и экспериментальной медициныunclassified